2017
DOI: 10.4055/jkoa.2017.52.6.521
|View full text |Cite
|
Sign up to set email alerts
|

The Proximal Approach in an Ultrasound-Guided Suprascapular Nerve Block

Abstract: Purpose: The purpose of this study was to analyze any effectiveness, advantages, and the procedure of an ultrasound-guided suprascapular nerve block via the proximal approach in patients suffering from shoulder pain. Materials and Methods:A total of 51 patients treated with nerve block between November 2015 and November 2016 were analyzed. We identified the suprascapular nerve that branches off the superior trunk of the brachial plexus, and found the suprascapular nerve, which is located in the fascial layer b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…Besides, the technique using the inferior belly of the omohyoid muscle as the landmark of SSN identification has been described (Battaglia et al). The possibility of SSN visualization using this technique was 90-96 % (Rothe et al;Ko et al, 2017). These previously reported results were similar to our study in that the SSN at the supraclavicular region was correctly identified in 90 % of cases.…”
Section: Discussionsupporting
confidence: 91%
“…Besides, the technique using the inferior belly of the omohyoid muscle as the landmark of SSN identification has been described (Battaglia et al). The possibility of SSN visualization using this technique was 90-96 % (Rothe et al;Ko et al, 2017). These previously reported results were similar to our study in that the SSN at the supraclavicular region was correctly identified in 90 % of cases.…”
Section: Discussionsupporting
confidence: 91%